Integrative Assessment Model Of Language Skills (Listening, Reading, Speaking, Writing) - Maktuba, Khonsaidova; Oblaberganova Marhabo Maxmudjon qizi (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
This article examines the integrative assessment model as an alternative to traditional discrete-point testing. The study explores how listening, reading, speaking, and writing can be assessed simultaneously through task-based approaches. Drawing on established theories of communicative competence and performance-based assessment, the research employs a mixed-methods design involving university-level students. The findings demonstrate that integrative assessment enhances validity, promotes learner engagement, and provides a more comprehensive evaluation of language proficiency. The paper concludes by recommending the adoption of integrative models in higher education contexts.